Short-term outcomes associated with fluoxetine, low-frequency rTMS, and their combination in first-onset adolescent OCD: a single-center retrospective cohort - Yang, Zhenzhen; Hu, Chunfeng; Wang, Huan; Yang, Tao; Wang, Haixia; Jiang, Meng (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to compare the short-term clinical outcomes of low-frequency repetitive transcranial magnetic stimulation (LF-rTMS), fluoxetine, and their combination in adolescents with first-onset obsessive-compulsive disorder (OCD) using a single-center retrospective, non-randomized design.MethodsA single-center retrospective, non-randomized analysis was conducted on 167 adolescents (aged 12–18 years) diagnosed with obsessive-compulsive disorder (OCD) and treated at Dazhuang Hospital, Shandong Province, between January 2018 and June 2024. Based on treatment received, patients were categorized into three observational groups: LF-rTMS alone (n=32), fluoxetine alone (n=55), and combined fluoxetine plus LF-rTMS (n=80). LF-rTMS was delivered at 1 Hz over the right supplementary motor area (SMA), 20 sessions in total. Clinical outcomes were assessed using the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS), Clinical Global Impressions-Improvement (CGI-I), Wisconsin Card Sorting Test (WCST), and quantitative electroencephalography (qEEG) at baseline, 2 weeks, and 4 weeks. Adverse events were monitored with the Treatment Emergent Symptom Scale (TESS).ResultsAfter 4 weeks of treatment, 68.26% of patients overall met the predefined response threshold (≥35% Y-BOCS reduction), with rates of 34.38% in the LF-rTMS group, 63.64% in the fluoxetine group, and 85.00% in the combined treatment group; remission (Y-BOCS ≤12) was observed in 12.5%, 20.0%, and 32.5% of the groups, respectively (χ²=27.85, P<0.001). Repeated-measures analyses further indicated significant Time and Time×Group effects for both Y-BOCS and CGI-I scores (P<0.001), confirming differential symptom trajectories across treatment groups. The combined group also showed comparatively greater improvements in cognitive performance (WCST indices) and more favorable qEEG changes relative to the monotherapy groups (P<0.001). No statistically significant differences in the distribution of adverse reactions were observed among the three groups (P = 0.549).ConclusionThe findings suggest that combining fluoxetine with LF-rTMS may be associated with greater short-term improvements in symptom severity, cognitive function, and neural activity compared with monotherapy, while maintaining a favorable safety profile.